Managing Cultural Festivals Tradition and Innovation in Europe (Taylor & Francis, 2022)
book fairs, creative industries, cultural effects, digital age, food events, management, music festivals, organization, publishing, strategy, UNESCO heritage, Venice Biennale
English
Keywords: Pageants, parades, festivals; book fairs, creative industries, cultural effects, digital age, food events, management, music festivals, organization, publishing, strategy, UNESCO heritage, Venice Biennale